Cognitional conditions of short-term memory in motor learning - Czyz, S.; Starosciak, W.; Bilinski, W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Atkinson and Shiffrin` theory of memory published in 1968 [1] described two different types of memory: short-term memory (STM) and long-term memory (LTM). However, very soon, the concept of levels of processing information [2] dominated research in the area of memory [3]. We wanted to look at the interference during memorising - different types of activities caused interference. We looked at motor learning, phonetic loop, UBS memory [4]. We considered the depth of processing information. Methods We divided subjects into three groups (30 persons each). All groups were asked to remember 6 digit number (presented for 2 sec.). Then, they were asked to watch a movement (with 12-sequences). They had to memorise this movement watching a video-cassette (15 seconds) -sequences were taken from Latinek`s Motor Capability Test [5]. Subjects were asked to reproduce the movement (movement time about 12 sec). After this time (max. 30 sec.) they had to recall the 6-digit number. Three groups differed one from another in the phase of memorising the movement. First group had to watch the video and simultaneously subjects from this group were asked to describe the sequences they were watching. While reproducing the movement they described it again. Subjects from the second group while watching the video, listened to a fairy tale (very short one - 25 sec.). They recall the story reproducing the movement. Third group simply watched the cassette and then reproduced the movement. We used nonparametric Spearman` correlation, Mann-Whitney` U-test, Kruskal- Wallis` test. All subjects did a CORSI test - direct memory, using Vienna Test System. Results We compared the results of remembered numbers (6 digit numbers), the number of sequences correctly remembered, CORSI results (to differ subjects and as a co-variable). There was no difference between groups divided depending on the depth of processing information. We found however, strong correlation between groups depending on UBS results (CORSI test).